Ã¢â‚¬ËœUrf dalam Kompilasi Hukum Islam Indonesia - Hamzawi, Adib (Ali Muchasan, 2018)
'Urf is one of the methods of ijtihad to establish a law of problems which does not contain its provisions in the Qur'an or hadith. The legal construct built by the 'urf is considering the local aspect of wisdom, since the neglect of the 'urf tends to ignore the welfare of society that is the object of the law itself. The benchmark of Islamic jurisprudence in Indonesia uses legal formulation in the Compilation of Islamic Law as its reference. In other words, Compilation of Islamic Law is the legal jurisprudence of Indonesia. This paper examines how the role of 'urf in the formulation of the articles of Compilation of Islamic Law and how the contribution of 'urf in the development of Islamic law in Indonesia. This study is a literature research with normative juridical approach, ie reviewing the articles of Compilation of Islamic Law as data analyzed. The analysis uses the us u @ l al-fiqh theory of 'urf, to know the extent of the role of' urf in those chapters. The results of the study found that 'urf became one of the foundations of the formulation of the articles of Compilation of Islamic Law. Of the 229 Articles of Compilation of Islamic Law, there are 33 articles that accommodate Indonesian customs. The articles govern marriage, property, bilateral inheritance, peace agreements in inheritance, inheritance, collective inheritance, joint property inheritance, and wills . In addition to the formulation of those articles, the Compilation of Islamic Law requires judges to always explore the principles of the living law in society through the provisions of the closing in Article 229.